Pendampingan Penyusunan Strategi Pemasaran Tas Kulit dalam Menghadapi Persaingan Global di Dukuh Tengah Desa Nambangrejo Sukorejo Ponorogo - Jailani, Ahmad; Khafidhoh, Khafidhoh (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This mentoring is motivated by a leather bag entrepreneur, Mr. Agus, who is currently related to competition between local products and imported products. Imported products produce products that are the same shape as local crafts, only the materials are different, but people's interest is more interested in choosing imported products because the prices are more affordable. This mentoring aims to analyze the marketing and branding strategies that must be implemented by Mr. Agus, a leather bag craftsman in Dukuh Tengah, Nambangrejo Village in facing competition with imported products. Globalization makes it easier to access imported products, so Mr. Agus faces a big challenge to maintain their market. The research method used is qualitative with the ABCD approach with existing asset developers. Data collection techniques are carried out through observation, interviews, and documentation. Based on the results of the mentoring, product differentiation through material quality, unique design, and local cultural values ​​are the main keys to maintaining the existence of local leather bag products. In addition, the use of social media as a branding and marketing tool has proven effective in increasing brand awareness and expanding market reach. Recommendations are given for Mr. Agus to focus more on developing a strong brand identity and improving digital marketing skills to compete more effectively in the global market.